3D analytical and numerical modelling of the regional topography influence on the surface deformation due to underground heat source - BRIMICH, Ladislav; CHARCO, María; KOHÚT, Igor; FERNÁNDEZ, José (Contributions to Geophysics and Geodesy, 2011)
Thermo-elastic strains and stresses play a considerable role in the stress stateof the lithosphere and its dynamics, especially at pronounced positive geothermal anomalies.Topography has a significant effect on ground deformation. In this paper we describetwo methods for including the topographic effects in the thermo-viscoelastic model. Firstwe use an approximate methodology which assumes that the main effect of the topographyis due to distance from the source to the free surface and permits to have an analyticalsolution very attractive for solving the inverse problem. A numerical solution using FiniteElement Method (FEM) is also computed. The numerical method allows to includethe local shape of the topography in the modelling. In the numerical model the buriedmagmatic body is represented by a finite volume thermal source. The temperature distributionis computed by the higher-degree FEM. For analytical as well as numerical modelsolution only the forces of thermal origin are considered. The comparison of the resultsobtained using both analytical and numerical techniques shows the qualitative agreementof the vertical displacements. In the numerical values small differences were obtained.The results show that for the volcanic areas with an important relief the perturbationof the thermo-viscoelastic solution (deformation and total gravity anomaly) due to thetopography can be quite significant. In consequence, neglecting topography could giveerroneous results in the estimated source parameters.